Parental support of the Canadian 24-hour movement guidelines for children and youth: prevalence and correlates - Ryan E. Rhodes; John C. Spence; Tanya Berry; Guy Faulkner; Amy E. Latimer-Cheung; Norman O'Reilly; Mark S. Tremblay; Leigh Vanderloo (BMC, 2019)
Abstract Background To explore the prevalence of parental support for meeting the Canadian 24-Hour Movement Guidelines for Children and Youth, identify key interactive support profiles among the four movement behaviors, and investigate subsequent sociodemographic and social cognitive correlates of these profiles. Methods A sample of Canadian parents (N = 1208) with children aged 5 to 17 years completed measures of the theory of planned behavior (TPB), and support of the four child movement behaviors via questionnaire. Differences in the proportion of parents supporting these four health behaviors were explored and demographic and social cognitive (attitude and perceived control) correlates of combinations of parental support for the four health behaviors were evaluated. Results Child and youth sleep behavior had the highest parental support (73%) and moderate to vigorous physical activity support had the lowest prevalence (23%). Interactive profiles of the four movement behaviors yielded six primary clusters and comprised wide variation from parents who supported none of these behaviors (19%), to parents who supported all four behaviors (14%). These profiles could be distinguished by the age of the child (younger children had higher support) and the gender of the parent (mothers provided more support), as well as constructs of the TPB, but TPB cognitions were more specific predictors of each health behavior rather than general predictors of aggregate health behavior clusters. Conclusions Teenagers and fathers may represent key targets for parental support intervention of the 24-Hour Movement Guidelines. Intervention content may need to comprise the underlying foundations of attitude and perceived behavioral control to change parental support while considering the unique features of each health behavior to maximize related intervention effectiveness.